Integrated serological surveillance of communicable diseases in the Paraguayan Chaco, 2019 - Patricia Galeano; Claudia Huber; Violeta Ortiz; Soraya Araya; Vilma Teresa Pérez; Guillermo Sequera; María Paz Ade; Gloria Rey-Benito; Pamela Bravo; Ana Luciañez; Romeo Montoya; Silvia Giselle Ibarra-Ozcariz; et al. (Revista Panamericana de Salud Pública)
Objective. To establish baseline seroprevalence of soil-borne, waterborne, and foodborne diseases and to monitor diseases that are eliminated or on the path to elimination in the Paraguayan Chaco. Methods. A total of 1 100 school-age children (6–15 years) were tested in urban and rural schools selected for a cross-cutting population-based survey using a two-stage probabilistic sample design in the three departments of the Paraguayan Chaco. Blood samples were taken on filter paper to measure IgG antibodies using a multiplex bead assay. Data collection was carried out through interviews with parents and caregivers. Access to basic sanitation and improved water was assessed. Differences in pathogen seropositivity and seroprotection were estimated by urban and rural areas. Results. Seroprotection against measles was 62.9% and against rubella was 78.2%. Minimal diphtheria and tetanus seroprotection (≥0.01 IU/ml) was 92.9% and 98.3%, respectively. Seroprotective levels against these four vaccine-preventable diseases significantly decreased with increasing age (p < 0.05). The following pathogens and respective antigens showed significantly higher seroprevalence (p < 0.05) in rural areas compared with urban areas: Cryptosporidium parvum Cp17: 80.4% vs 64.6%, and Cp23: 60.6% vs 44.8%; Giardia lamblia VSP3: 26.9% vs 16.6%; Strongyloides stercoralis NIE: 11.5% vs 4.1%; and Taenia solium T24H: 7.1% vs 1.6%. Seroprevalence for these pathogens was also higher in Indigenous population when compared to non-Indigenous. Basic sanitation conditions showed significant differences (p < 0.05) between rural and urban areas: adobe and soil dwelling floor (65.3% vs 30.2%), use of pit latrine (90.3% vs 44.2%), availability of drainage or septic tank (8.7% vs 55.2%), access to safe water (19.7% vs 44.9%), and water treatment (6.8% vs 32.3%). Conclusions. We identified high exposure to soil-borne, waterborne, and foodborne diseases in rural areas and Indigenous population in the Paraguayan Chaco. Low seroprotection against measles and rubella alerts about the risk of immunity gaps to maintain elimination targets.